MENIMBANG ULANG ETIKA MORAL âABD AL-JABBAR Kajian atas Islamic Rationalism: The Ethics of âAbd al-Jabbar karya GF Hourani - Affandi, Abdullah (Jurnal al Hikmah, 2017)
GF. Hourani points out that other writings usually describe ethics in philosophical perspectives such as Miskawayh and al-Tusi, especially with regard to the classification and description of evil and goodness based on the treatment of Aristotle in Nikomakean ethics. He also realizes that values and ethical theories can be reconstructed from the work of eminent philosophers, but their basis is usually Neoplatonian and Aristotelian. Such books, according to Hourani offer little new general philosophical interest. Therefore, he considered that the Mutazila was the first Islamic moralist. He reconstructs a